Model Of Managing Developmental Language Disorder In Central Java - Arif Siswanto; Hafidz Triantoro Aji Pratomo (Poltekkes Kemenkes Surakarta, 2022)
Background: Language disorder is a neurodevelopmental disorder needing sustainable action. A speech therapist, as a member of the management team, has an obligation to solve a problem. In order to develop an intervention model for developmental language disorder, clinician perception is required. Methods: The research was conducted using a survey approach. The survey was conducted online through Google Forms, and the analysis was done using the statistical descriptive method. To see the inter-variable correlation, Spearman’s rank correlational test was used. Results: Descriptive statistics show varying data between one variable and another. Some points that become part of the majority’s perception are the frequency of intervention (3 times per week), the duration of the intervention (31–45 minutes), the informal assessment, and the multidisciplinary model. Assessment, ethnocultural, collaboration, and intervention variables all have an inter-variable relationship. The value of the assessment-to-intervention variable relation is p = 0.001, with r = 0.544. The value of the ethnocultural–to–intervention variable relation is p = 0.002, with r = 0.515. The value of the collaboration-to-intervention variable relation is p = 0.021, with r = 0.401. Conclusion: Further investigation using other research designs is required to reveal the need for language disorder intervention in Central Java. Descriptive data show that the management of language disorder in Central Java needs some requirements to be met.